Schistosomal pulmonary hypertension: a case report - Saraçlar, Muhsin; Tınaztepe, Behçet; Öztürk, Mustafa; Ertuğrul, Ali (The Turkish Journal of Pediatrics, 1972)
A case of schistosomal cor pulmonale in an 8-year-old Saudi Arabian boy is described for the first time in Turkish medical literature.The patient was referred to Hacettepe Children’s Hospital for evaluation of congenital heart disease, and after appropriate studies in Hacettepe Children’s Hospital the correct diagnosis was established.Clinical and pathological features of the disease, pathogenesis of pulmonary hypertension and a brief review of the literature are presented.